2001
DOI: 10.1116/1.1371322
|View full text |Cite
|
Sign up to set email alerts
|

Chlorosilane adsorption on clean Si surfaces: Scanning tunneling microscopy and Fourier-transform infrared absorption spectroscopy studies

Abstract: Articles you may be interested inDissociation mechanism of 2-propanol on a Si(111)-(7×7) surface studied by scanning tunneling microscopy Adsorption of atomic hydrogen on the Si(001) 4×3-In surface studied by coaxial impact collision ion scattering spectroscopy and scanning tunneling microscopy J. Vac. Sci. Technol. B 17, 983 (1999); 10.1116/1.590680In situ Fourier transform infrared spectroscopy and stochastic modeling of surface chemistry of amorphous silicon growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Silane and its halogen derivatives SiH 4-n X n are widely used as source gases in CVD fabricating silicon films. [1][2][3][4][5][6][7] It has long been observed that B 2 H 6 , a p-type dopant, mixed with SiH 4-n X n can catalyze the deposition. Boron doping efficiency and the rate of film deposition are greatly influenced by variation of the B 2 H 6 concentration and the species of SiH 4-n X n .…”
Section: Introductionmentioning
confidence: 99%
“…Silane and its halogen derivatives SiH 4-n X n are widely used as source gases in CVD fabricating silicon films. [1][2][3][4][5][6][7] It has long been observed that B 2 H 6 , a p-type dopant, mixed with SiH 4-n X n can catalyze the deposition. Boron doping efficiency and the rate of film deposition are greatly influenced by variation of the B 2 H 6 concentration and the species of SiH 4-n X n .…”
Section: Introductionmentioning
confidence: 99%
“…Dichlorosilane (SiH 2 Cl 2 ) preferentially reacts at corner holes, and the dissociated chlorin atoms adsorb at neighboring corner adatoms. 7) Methanol (CH 3 OH) selectively reacts with adatoms, with its -OCH 3 attaching to adatoms and its hydrogen to rest atoms 8) and water (H 2 O) dissociates into -OH at the adatom and -H at the rest atom. 9) From these results, it is found that the dissociative adsorption on the Si(111)-7Â7 surface occurs at adatoms, rest atoms, and corner holes.…”
Section: Resultsmentioning
confidence: 99%